The Dynamics of Politeness in Online Interaction: A Study of Code-Switching and Code-Mixing on the Youtube Platform - Septiana, Amelya (Universitas Negeri Jakarta, 2024)
This study aims to examine the phenomenon of code switching and code mixing in online interactions on the Youtube platform, with data sources in the form of speech taken from the Youtube video channel “Nihongo Mantappu Waseda Boys Trip to Indonesia edition”. The research method used is descriptive qualitative. The results showed the existence of internal code switching between languages, namely from Indonesian to Javanese. In addition, external code switching between languages was also found, namely from Indonesian to Japanese, from Japanese to English, and from Indonesian to English. The code-mixing found in this study includes the addition of particles, words, phrases, and sentences. This research also makes an important contribution in understanding the dynamics of politeness in online interaction, especially in the Youtube platform.